1980
DOI: 10.2172/5381758
|View full text |Cite
|
Sign up to set email alerts
|

Identification of technical problems encountered in the shallow land burial of low-level radioactive wastes

Abstract: Under Contract No. 11V-13619V March 1980 NOTICE. This document contains information of a preliminary nature. It is subject to revision or correction and therefore does not represent a final report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Operating experience, dating back to the early 1940s at major lowlevel radioactive waste disposal sites, has shown that interactions of water with the landfill covers caused most containment failures (Duguid, 1977;Jacobs et al, 1980;Hakonson et al, 1982;Herzog et al, 1982). It has also been shown that landfill covers are susceptible to failure during snowmelt periods when large inputs of water occur when evapotranspiration is low (Nyhan et al, 1990).…”
Section: Few Field Studies Have Been Conducted T O Evaluate the Relatmentioning
confidence: 99%
“…Operating experience, dating back to the early 1940s at major lowlevel radioactive waste disposal sites, has shown that interactions of water with the landfill covers caused most containment failures (Duguid, 1977;Jacobs et al, 1980;Hakonson et al, 1982;Herzog et al, 1982). It has also been shown that landfill covers are susceptible to failure during snowmelt periods when large inputs of water occur when evapotranspiration is low (Nyhan et al, 1990).…”
Section: Few Field Studies Have Been Conducted T O Evaluate the Relatmentioning
confidence: 99%
“…The most serious problems encountered in shallow land burial of wastes are related to water management (Jacobs et al, 1980;Fisher, 1986;Nativ, 1991). The movement of water through buried wastes is recognized as a major mechanism for transporting wastes beyond their original burial boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…1). The most serious problems encountered in shallow land burial are related to water management (Jacobs et al 1980). As water comes into contact with the buried wastes, either from infiltration of precipitation or from trench cap erosion and subsidence, the integrity of the buried wastes is breached.…”
mentioning
confidence: 99%